How do relational and personal attributes affect trust in adolescent friendship: An exploratory model - Ainin Rahmanawati; Flaviana Rinta Ferdian; Tria Widyastuti; Faturochman Faturochman; Wenty Marina Minza (Universitas Ahmad Dahlan, 2020)
Trust is an important aspect in human relationship. According to previous research trust is influenced by 2 main attributes: personal (benevolence, integrity, and competence) and relational (support, closeness, and reciprocity) attribute. The study aimed to find a preliminary model to explain the association of personal and relational attributes in adolescent friendship. Two hundred and twenty participants (male=44.09% and female=55.91%) participated in the study. A survey method was used to collect the data. The design of this study was correlational design. Results from enter method in regression analysis show that six factors of personal and relational attributes influence trust at 44.5%. However, closeness had no significant influence on trust, so closeness was not included in the next analysis, the sequential analysis. The result shows that the relational attribute has higher influence on trust than personal attribute. Support and reciprocity factors which belong to relational attribute, has a higher contribution to trust in adolescent friendship than benevolence, integrity and competence – the latter three factors belonging to the personal attribute. Therefore building trust in friendship requires an emphasis on relational attributes of trust, especially that of support and reciprocity factors.